Legal Analysis of Restitution Granting as an Effort to Restore the Rights of Victims of Sexual Violence in the Perspective of Indonesian Positive Law Based on Justice Values - Irawan, Ridho Hendry; Arpangi, Arpangi (Jurnal Hukum Khaira Ummah, 2025)
Abstract. Sexual violence is a violation of human rights that injures the dignity and honor of the victim, and requires recovery through restitution. Even though it has been regulated in Indonesian positive law, the implementation of providing restitution for victims of sexual violence still faces various challenges. The aim of this research is to analyze the current arrangements for providing restitution as an effort to restore the rights of victims of sexual violence, to analyze the weaknesses of the system of providing restitution as an effort to restore the rights of victims of sexual violence in the perspective of positive Indonesian law, and to analyze the ideal arrangements for providing restitution as an effort to restore the rights of victims of sexual violence in the perspective of positive law in Indonesia in the future based on justice. The aproach method used in preparing the thesis is normative juridical research. The specifications in this research are descriptive analysis. The theories used include legal certainty theory, legal system theory, justice theory. The results of this research are (1) Regulations regarding the provision of restitution in cases of criminal acts of sexual violence have been regulated in Law Number 12 of 2022 and Supreme Court Regulation Number 1 of 2022. Restitution is recognized as a victim's right which must be exercised by the perpetrator or a third party. (2) Weaknesses in the substance of current regulatory law are that they are unable to provide protection for victims because they still place victims as objects in the criminal justice system. Weaknesses in legal culture which is still influenced by patriarchy and negative stereotypes towards women. (3) The ideal arrangement for providing restitution as an effort to restore the rights of victims of sexual violence requires the presence of a legal system that is not only based on normative justice as regulated in the TPKS Law and its derivative regulations, but is also realized substantively through real fulfillment of the victims' rights, including when the perpetrator is unable to pay. The imbalance between norms and implementation shows the need for improvement, especially in the state's role in ensuring the recovery of victims through compensation mechanisms, in order to achieve complete justice as described by Hans Kelsen, that the law must aply generally and regularly, where the state needs to ensure that victims' rights can be realized in real terms as a form of the state's responsibility in protecting its citizens.